Role Playing with Behavioristic Approach on Interpersonal Communication Skills of Students in Senior High School - Sari, Yulia Novita; Kusumawati, Kusumawati (International Journal of Applied Guidance and Counseling, 2023)
Interpersonal communication skills is communication that is carried out between two or more people, both verbal and nonverbal to students. In fact, at school there are still many students who have less interpersonal communication skills in interactions such as frequent misunderstandings in communicating at school. Seeing this phenomenon, efforts are needed to improve students' interpersonal communication skills. The purpose of this study is to increase students' self-confidence and to determine the effectiveness of role playing with a behavioristic approach to students' interpersonal communication skills. The method used in this research is quasi-experimental research with Nonequivalent Control Groups Design. The results show that t count = 8.616 > t table = 1.999. So, the conclusion Ho is rejected and Ha is accepted, which means the use of role playing with a behavioristic approach can improve students' interpersonal communication skills.